Formal indications in the trademark (Arab institutions as a model) - Hashem Zeki Muhammad Ali; Qais Eesa Abdullah (Basrah Arts Journal, 2023)
emantics and ways to employ them in the brand have made a big difference in the field of visual art in general since ancient times, I mean since the first practices of ancient man on the walls of caves, he was satisfied with encoding things and writing them down from his daily observations, so they seemed simple and spontaneous, from here symbolic signs and signs were formed and became a semantic meaning and a functional purpose in his life. Art had the largest share through the employment and borrowing of these forms in contemporary works of art, no matter how distinctive the work of art is, we find its root and basis based on the forms provided by nature, we see its clear impact on the brand and what is borrowed to form a clear visual discourse with a beautiful vision with a functional dimension according to a system governed by artistic formats that are characterized by an academic formulation of the brand of Arab institutions. Results of the article : - 1- Man, especially the artist and designer, has borrowed and employed all the natural, industrial and harmonic symbols surrounding him in most of his daily life. 2- The symbol is no longer only for cognitive communication, but it had another function, which is deliberative through commodification, an identity associated with the product and private ownership .